2018
DOI: 10.3390/toxins10110475
|View full text |Cite
|
Sign up to set email alerts
|

Patulin in Apples and Apple-Based Food Products: The Burdens and the Mitigation Strategies

Abstract: Apples and apple-based products are among the most popular foods around the world for their delightful flavors and health benefits. However, the commonly found mold, Penicillium expansum invades wounded apples, causing the blue mold decay and ensuing the production of patulin, a mycotoxin that negatively affects human health. Patulin contamination in apple products has been a worldwide problem without a satisfactory solution yet. A comprehensive understanding of the factors and challenges associated with patul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 165 publications
0
65
0
1
Order By: Relevance
“…It is known that patulin is mainly produced in rotten parts of the fruits (Cheraghali et al 2005). Zhong et al (2018) reported that patulin has been constantly detected in apple products made from externally healthy apples that have internal rot which is not omitted before pressing. However, Soliman et al (2015) reported that several fungal species may inhabit the core of the fruit that appears visually blemish free.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that patulin is mainly produced in rotten parts of the fruits (Cheraghali et al 2005). Zhong et al (2018) reported that patulin has been constantly detected in apple products made from externally healthy apples that have internal rot which is not omitted before pressing. However, Soliman et al (2015) reported that several fungal species may inhabit the core of the fruit that appears visually blemish free.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed by Kalinowska et al (2014), the concentration of individual phenolic compounds in apples depends on the cultivar, maturity of the fruit, cultivation conditions, harvest, storage and infections. Phenolic compounds have an important role as defence mechanisms against pathogens and patulin (Cushnie and Lamb 2005, Ferreyra et al 2012, Sun et al 2017, Zhong et al 2018. However, which particular pathogens induce the formation of phenolic compounds, is usually not specified.…”
Section: Factors Affecting Polyphenol Concentration In Apple Juicesmentioning
confidence: 99%
“…Mainly associated with fruits including grapes, pears, pineapples, peaches and remarkably apples and products thereof (Zhong, Carere, Lu, Lu, & Zhou, 2018). (Zhong et al, 2018).…”
Section: Patulinmentioning
confidence: 99%
“…For the past few years, researchers have been exploring strategies to reduce patulin contamination in apple and apple products (Ge, Xu, Li, Peng, & Pan, 2017; Zhong, Carere, Lu, Lu, & Zhou, 2018). Different control strategies in mold elimination have been proposed, such as washing, getting rid of moldy tissue, and keeping storage conditions at appropriate temperatures and atmosphere (Salomão, Aragão, Churey, Padilla‐Zakour, & Worobo, 2009), but these strategies do not reduce toxin levels completely to safe levels.…”
Section: Introductionmentioning
confidence: 99%
“…Different control strategies in mold elimination have been proposed, such as washing, getting rid of moldy tissue, and keeping storage conditions at appropriate temperatures and atmosphere (Salomão, Aragão, Churey, Padilla‐Zakour, & Worobo, 2009), but these strategies do not reduce toxin levels completely to safe levels. Therefore, some physical or chemical methods were applied to reduce patulin in apple products, including sulfur dioxide, irradiation, active carbon, vitamins, high hydrostatic pressure, and adsorbents (Ioi et al., 2017, Zhong et al., 2018). Among them, adsorption has been of interest to the juice industry in the last few years due to its obvious advantages of high efficiency, cost effective, simple operation, and nonsecondary pollution (Gong et al., 2015; Wang, Zhang, & Liu, 2017).…”
Section: Introductionmentioning
confidence: 99%